Building Collaborative Partnerships to Improve Public Health Services in Bumi Ayu - Erinaldi Erinaldi; Dede Mirza; Sutrisno Sutrisno; Delfira Nurroma (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Health services are one of the fundamental needs of society and play a crucial role in determining quality of life and social welfare. However, limited access to routine health check-ups and low public awareness of the importance of early disease detection remain significant challenges in many areas, including Bumi Ayu Village. This Community Service Program (PKM) aims to establish a partnership between STIA Lancang Kuning, local health centers, and the community to improve health services through basic health examinations. The program was implemented using health education sessions, interactive discussions, and continuous monitoring and evaluation. The health examinations included blood glucose, cholesterol, blood pressure, and uric acid checks. The results indicate an improvement in community knowledge and awareness regarding the importance of routine health examinations as a preventive measure against disease. Active community participation throughout the program reflects positive acceptance of the established partnership model. This activity demonstrates that collaboration between higher education institutions, health professionals, and the community can serve as an effective strategy to enhance the quality of local health services.